Somatostatin, Olfaction, and Neurodegeneration - Saiz-Sanchez, Daniel; Ubeda-Bañon, Isabel; Flores-Cuadrado, Alicia; Gonzalez-Rodriguez, Melania; Villar-Conde, Sandra; Astillero-Lopez, Veronica; Martinez-Marcos, Alino (Frontiers in Neuroscience, 2020)
Alzheimer’s and Parkinson’s diseases are the most prevalent neurodegenerative disorders in aging. Hyposmia has been described as an early symptom that can precede cognitive and motor deficits by decades. Certain regions within the olfactory system, such as the anterior olfactory nucleus, display the neuropathological markers tau and amyloid-β or α-synuclein from the earliest stages of disease progression in a preferential manner. Specific neuronal subpopulations, namely those expressing somatostatin (SST), are preferentially affected throughout the olfactory and limbic systems. SST is a neuropeptide present in a subpopulation of GABAergic interneurons throughout the brain and its main function is to inhibit principal neurons and/or other interneurons. It has been reported that SST expression is reduced by 50% in Alzheimer’s disease and that it is related to the formation of Aβ oligomers. The mechanisms underlying the preferential vulnerability of SST-expressing neurons in Alzheimer’s disease (and, to a minor extent, in Parkinson’s disease) are not known but analysis of the available data could shed light on their etiology. This short review aims to update the knowledge of functional features of somatostatin within the olfactory system and its role in olfactory deficits during neurodegeneration.